Modeling Biowaste Biorefineries: A Review - De Buck, Viviane; Polanska, Monika; Van Impe, Jan (Frontiers in Sustainable Food Systems, 2020)
The biorefining of biowaste is an upcoming novel strategy, but is mostly still in its conceptual phase. Biowaste biorefineries would allow (rural) communities to convert their biowaste into value-added biofuels, biochemical compounds, and fertilisers. Several different types of biowaste biorefineries have already been developed, but little to none of these designs are already commercially exploited. Their further development and commercial implementation is hampered by the high investment costs and risks, little trusts in its novel technologies, expected yields and profits, and operating reliability. Modelling these integrated processes, together with their supply chains, would allow for optimising the considered biorefinery designs and coincidently speeding up the R&D-process. The optimised biorefinery designs and supply chains would additionally embed an increased amount of trust in potential investors in terms of the economic sustainability of the considered novel processes. Therefore, in this publication, a summary of existing biorefinery models is presented, together with supply chain network models. The discussed biorefinery models are categorised according to the conversion platform they use, being thermochemical, biological, or hybrid ones. Furthermore, the overall inherent advantages and disadvantages of all conversion platforms are summarised and a scope of further research needs is presented.